2022
DOI: 10.3390/app12052564
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons and Polychlorinated Biphenyls in Seawater, Sediment and Biota of Neritic Ecosystems: Occurrence and Partition Study in Southern Ligurian Sea

Abstract: The Mediterranean Sea is subjected to a high anthropic pressure, which determines direct or indirect discharges of persistent organic pollutants deriving from intensive industrial activities. These compounds could easily enter and contaminate the whole marine compartment, with possible transfers (and contamination) among water, sediment and biota. Based on the above-mentioned assumptions, in this work we studied the presence of 16 polycyclic aromatic hydrocarbons (PAHs) and 14 dioxin and non-dioxin-like polych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(54 reference statements)
1
4
1
Order By: Relevance
“…In comparison to other studies, overall values were relatively lower than those reported in Italy [28,45]. In fact, except for the data reported for Tunisia [27], the ΣPAH ranges found in this study were several folds lower than those observed in some coastal sediments from Libya, Turkey, Greece, or other points of Spain (Table S10) [46][47][48].…”
Section: Abiotic Compartment: Sedimentcontrasting
confidence: 89%
See 3 more Smart Citations
“…In comparison to other studies, overall values were relatively lower than those reported in Italy [28,45]. In fact, except for the data reported for Tunisia [27], the ΣPAH ranges found in this study were several folds lower than those observed in some coastal sediments from Libya, Turkey, Greece, or other points of Spain (Table S10) [46][47][48].…”
Section: Abiotic Compartment: Sedimentcontrasting
confidence: 89%
“…In this study, LOQs oscillated between 0.001-1.701 µg kg −1 d.w., 0.091-4.363 µg kg −1 d.w, and 0.007-1.056 µg kg −1 d.w. for leaves, rhizomes, and sediments, respectively. These LOQs were lower or similar to those presented in analogous studies [45,46]. The LODs obtained in this study varied from 0.0003 to 0.5103 µg kg −1 d.w., 0.0273 to 1.3089 µg kg −1 d.w., and from 0.0021 to 0.3168 µg kg −1 d.w. for leaves, rhizomes, and sediments respectively.…”
Section: Extraction Procedures Optimization and Validationsupporting
confidence: 81%
See 2 more Smart Citations
“…Rivoira et al [8] studied the presence of 16 polycyclic aromatic hydrocarbons (PAHs) and 14 dioxin-and non-dioxin-like polychlorinated biphenyls (PCBs) in the neritic protected marine area of the Southern Ligurian Sea (Mediterranean Sea), affected by the impact of human activities. The study was focused on the possible partition of micropollutants within seawater, sediment, and zooplankton.…”
Section: Effects Of Contamination On Marine Organismsmentioning
confidence: 99%